Mental health of unaccompanied refugee minors in Europe: A systematic review. (November 2022) - Daniel-Calveras, Andrea; Baldaquí, Nuria; Baeza, Inmaculada
Abstract: Background: Nearly half of the refugee and asylum seeking population in Europe is under the age of 18, and many of these individuals are unaccompanied children and adolescents. Objective: The aim of this systematic review is both to summarize findings regarding the prevalence of mental health disorders among unaccompanied refugee minors (URM) in European countries since the last available systematic review (October 2017), and to describe associated risk factors. Methods: Five databases were systematically searched for articles published between October 1, 2017 and May 1, 2022. Results: The findings from 23 studies conducted in 9 countries which examined 80, 651 child and adolescent URM are explained. Afghanistan was the most common country of origin in the majority of studies and >75 % of the subjects were boys. Most of the studies ( N = 13, 56.5 %) assessed posttraumatic stress disorder (PTSD) prevalence. We found a high prevalence of mental health disorders among URM children and adolescents, which varied considerably between studies, ranging from 4.6 % to 43 % for (PTSD), 2.9 % to 61.6 % for depression, 32.6 % to 38.2 % for anxiety and 4 to14.3 % for behavioral problems. Two studies looking at suicide attempts and deaths, also observed higher rates in URM compared to the host population of the same age. The studies looking at mental health risk factors suggest that levels of social support in the host country, rearing environment, and other factors are associated with psychopathology. Moreover, a meta-analysis of four studies regarding PTSD in URM and accompanied refugee minors (ARM) showed a lower prevalence among ARM: -1.14 (95%CI:-1.56—0.72). Conclusions: PTSD, depression and anxiety are the most prevalent problems among the URM population in Europe. Early intervention in host countries is needed in order to improve mental health outcomes for this vulnerable population and avoid possible neglect.